Analisis Pengaruh Zakat Produktif Terhadap Peningkatan Usaha Mikro (Studi kasus pada Mustahik BinaanYayaysan Dana Sosial Al-FalahCabang Kota Malang) - Kaffah, Silmi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Poverty in Indonesia is a major consideration because it is a problem in economics specifically inequality in terms of income, therefore the government looking for the solution of lowering the poverty by stimulate the society to increase a productive enterprise such as Small and Madium Enterprise (SME’s) along with assistance provided by Yayasan Dana Zakat Al-Falah (YDSF), therefore this research focused on the problems of the productive zakat effect for improvement of micro enterprises study case on Mustahik Binaan YDSF of Chapter Malang. This research apply quantitative method by descriptive approach and using multiple linear regression analysis and dummy regression. Using four variables such as venture capital, venture capital origin, training, and labor. The result of this research is the variable of venture capital and the capital of the business have positive and significant influence, the training and worker variables have positive and insignificant effect.Key word: YDSF, SME’s, Mustahik, Multiple Linear Regression Analysis, Zakat Produktif.